1963
DOI: 10.1017/s0007485300048483
|View full text |Cite
|
Sign up to set email alerts
|

The significance of BHC degradation in resistant house-flies

Abstract: Resistance to γ BHC and dieldrin in various insects usually gives a characteristic resistance spectrum, probably indicating a common defence mechanism. Resistant house-flies (Musca domestica L.) are slightly anomalous in showing greater tolerance of γ BHC than of endrin and isodrin, unlike other resistant strains. A possible explanation is that they can develop an additional defence, specific towards γ BHC, as well as the usual group resistance. This might well be enhanced enzymatic degradation of BHC, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1963
1963
1986
1986

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Observations on the nature of y-BHC/cyclodiene resistance.-The similarity in pattern of resistance shown by house-flies and blowflies, which was mentioned earlier, is not very surprising since it has been shown that resistance, to y-BHC and the cyclodiene insecticides is remarkably similar as regards toxicology and mode of inheritance in diverse arthropods (e.g., Busvine & Townsend, 1963). Characteristic resistance spectra are illustrated in fig.…”
Section: Resistance Levels Towards Various Compoundsmentioning
confidence: 72%
See 1 more Smart Citation
“…Observations on the nature of y-BHC/cyclodiene resistance.-The similarity in pattern of resistance shown by house-flies and blowflies, which was mentioned earlier, is not very surprising since it has been shown that resistance, to y-BHC and the cyclodiene insecticides is remarkably similar as regards toxicology and mode of inheritance in diverse arthropods (e.g., Busvine & Townsend, 1963). Characteristic resistance spectra are illustrated in fig.…”
Section: Resistance Levels Towards Various Compoundsmentioning
confidence: 72%
“…The normal house-fly strain was obtained from the Pest Infestation Laboratory, Slough, where it had been maintained for many years. The resistant colony derived from an American strain, obtained in 1958, and more recently reported on by Busvine & Townsend (1963). The two colonies of L. cuprina were those used by Busvine & Shanahan (1961).…”
Section: Insect Strainsmentioning
confidence: 99%
“…) In both cases, however, y BHC was used to assess resistance. Eecent work by Busvine & Townsend (1963) suggests that BHC-resistance in house-flies depends on more than one defence mechanism. Therefore it would not be surprising if they were inherited separately, and this would prevent agreement with predictions based on monofactorial inheritance.…”
Section: Discussion Of Results With Musca Domesticamentioning
confidence: 99%
“…Gammexane has been shown to be more rapidly metabolized by insecticide-resistant strains of houseflies than by susceptible flies (Bradbury & Standen, 1955;Sternburg & Kearns, 1956). Busvine & Townsend (1963) have put forward evidence to support the view that the mechanism of housefly resistance to Gammexane may consist oftwo factors, one being a common factor in insects responsible for cross-resistance to a range of chlorinated insecticides and not involving Gammexane metabolism, and the other being increased Gammexane detoxication, present in resistant houseflies but not in other insect species. In the present work no appreciable difference was found between enzyme preparations from Gammexane-resistant and -susceptible strains of houseflies when the amount of Cl-released from Gammexane was measured, nor was there any difference in glutathione-S-aryltransferase activities.…”
Section: Discussionmentioning
confidence: 99%